The Effect of Service Quality and Promotion on Patient Interest and Decision to Return, Mediated by Patient Satisfaction: (A Study in the THT Clinic of Linggajati Regional General Hospital, Kuningan, West Java) (International Journal of Economics and Management Research, 2025)
This research aims to analyze and empirically test the influence of Service Quality and Promotion on Patient Revisit Intention and Decision, with Patient Satisfaction as the mediating variable. This study was specifically conducted on patients at the Ear, Nose, and Throat (ENT) Polyclinic Area of Linggajati Regional General Hospital (RSUD Linggajati), Kuningan, West Java. This research employed an explanatory quantitative approach using a survey method. The research population was patients who had visited the ENT Polyclinic of RSUD Linggajati. The sample was taken using the accidental sampling technique, with a total sample size of 114 respondents. Primary data were collected through questionnaires. The data analysis technique used was Structural Equation Modeling (SEM) based on Partial Least Square (PLS), utilizing the SPSS version 26 software. The research findings indicate that service quality and promotion are significant and positive factors directly influencing patient satisfaction, patient intention, and revisit decision. Patient satisfaction was proven to significantly mediate the effect of promotion on both intention and revisit decision. Specifically, good service quality and promotion will enhance patient satisfaction, which in turn will strengthen the patients' intention and decision to seek treatment again.Therefore, the management of RSUD Linggajati is advised to focus on improving the dimensions of service quality, especially the aspects of service speed, accuracy of diagnosis, and the friendliness of medical staff, as well as ensuring that the promotion carried out is able to create positive expectations that can be met and converted into patient satisfaction, thereby leading to sustained visit loyalty.